Analiza i interpretacja wyników conjoint analysis - Rybicka, Aneta; Pełka, Marcin (Analysis and Interpretation of Conjoint Analysis Results, 2009)
The paper presents an analysis and interpretation of conjoint analysis results with a possibility of applying R software. The basic terms of conjoint analysis are presented. In the empirical part of the article, conjoint analysis procedure with application of R software is applied. To obtain such a goal data collected by students was used.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 185-193